2016
DOI: 10.18805/asd.v36i4.6472
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of high oleic acid content in new sourcesof groundnut (Arachis hypogaea L.)

Abstract: In view of growing importance of oil quality, an understanding of the inheritance of high oleic acid is essential to breed for high oleate groundnuts. Hence an investigation was undertaken to infer genes governing the high oleic acid in newly identified sources of groundnut. Number of crosses studied were one with low × medium (TAG 24 × TPG 41), two with low × high (TAG 24 × ICG 2381 and TAG 24 × 104 P51) and with one medium × high oleic acid (TPG 41 × 104 P 56) cross combinations during post rainy season of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…In 2010-2016 in India, crosses were made between peanut accessions with low, medium and high levels of oleic acid. The results confirmed that the enzyme that catalyzes the desaturation of oleic to linoleic acid is encoded by the genes FAD2A and FAD2B (Gangadhara and Nadaf, 2016). Also, it was found that this enzyme is encoded by two homologous genes (ahFAD2A and ahFAD2B) located in A and B subgenomes, respectively.…”
Section: Plant Sciencesupporting
confidence: 75%
“…In 2010-2016 in India, crosses were made between peanut accessions with low, medium and high levels of oleic acid. The results confirmed that the enzyme that catalyzes the desaturation of oleic to linoleic acid is encoded by the genes FAD2A and FAD2B (Gangadhara and Nadaf, 2016). Also, it was found that this enzyme is encoded by two homologous genes (ahFAD2A and ahFAD2B) located in A and B subgenomes, respectively.…”
Section: Plant Sciencesupporting
confidence: 75%